The effect of socioeconomic status and sex on emotional maturity quotient - Gaspay, Gemafiel Raga (1999)
This research was conducted to examine whether socioeconomic status and sex has significant effects on EMQ. This study involved 30 U.P. College students, who were deliberately selected from the randomly chosen first year to fourth year students with a total number of 52 students from U.P. Tacloban College, Tacloban City. For this, two research instruments were distributed, thus, demgraphic profile form, and EMQ test questionnaire among 52 students since there were two variables, namely the sex and socioeconomic status, considered in this study, A 2x3 factorial design was used. Each subtype of the first factor was composed of 15 subjects and each subtype of the second variable was comprised of 15. It was found out that each variable has no significant effect on EMQ at the .05 level. Likewise with the impact of the two variables when combined was insignificant.
Undergraduate thesis (B.A.S.S. Psychology) -- University of the Philippines, Tacloban.
Keywords: Socioeconomic status and sex effects on emotional maturity quotient; Social Science